Corporate governance mechanisms, sensitive factors and earnings management in Nigerian oil and gas industry - Miko, Nuraddeen Usman; Kamardin, Hasnah (Virtus interpress, 2016)
Oil and gas industry is considered as the sector that contributes a big share to the Nigeria economy.This study investigated the effects of corporate governance mechanisms, sensitive factors on earnings management of quoted oil and gas firms in Nigeria using the sample of nine (9) listed oil and gas firms for the period of ten years (2004-2013).Discretionary current accruals was used as the proxy for earnings management.Corporate governance mechanisms (boards size, chief executive officer (CEO) duality, directors’ ownership, audit committee size, audit committee independence), sensitive factors (corporate tax, corporate profit, corporate social responsibility) served as independent variables.The study concludes that corporate governance mechanisms curves earnings management while sensitive factors increase earnings management.The study recommends that corporate governance regulations should be strengthened to reflect present challenges.